Climate science strategy of the US National Marine Fisheries Service. (December 2016) - Busch, D. Shallin; Griffis, Roger; Link, Jason; Abrams, Karen; Baker, Jason; Brainard, Russell E.; Ford, Michael; Hare, Jonathan A.; Himes-Cornell, Amber; Hollowed, Anne; Mantua, Nathan J.; McClatchie, Sam; et al.
Abstract: Changes to our climate and oceans are already affecting living marine resources (LMRs) and the people, businesses, and economies that depend on them. As a result, the U.S. National Marine Fisheries Service (NMFS) has developed a Climate Science Strategy (CSS) to increase the production and use of the climate-related information necessary to fulfill its LMR stewardship mission for fisheries management and protected species conservation. The CSS establishes seven objectives: (1) determine appropriate, climate-informed reference points; (2) identify robust strategies for managing LMRs under changing climate conditions; (3) design decision processes that are robust to climate-change scenarios; (4) predict future states of ecosystems, LMRs, and LMR-dependent human communities; (5) determine the mechanisms of climate-change related effects on ecosystems, LMRs, and LMR-dependent human communities; (6) track trends in ecosystems, LMRs, and LMR-dependent human communities and provide early warning of change; and (7) build and maintain the science infrastructure required to fulfill NMFS mandates under changing climate conditions. These objectives provide a nationally consistent approach to addressing climate-LMR science needs that supports informed decision-making and effective implementation of the NMFS legislative mandates in each region. Near term actions that will address all objectives include: (1) conducting climate vulnerability analyses in each region for all LMRs; (2) establishing and strengthening ecosystem indicators and status reports in all regions; and (3) developing a capacity to conduct management strategy evaluations of climate-related impacts on management targets, priorities, and goals. Implementation of the Strategy over the next few years and beyond is critical for effective fulfillment of the NMFS mission and mandates in a changing climate. Graphical abstract: Highlights: Climate change is affecting marine ecosystems. Diversity, abundance, and distributions of living marine resources are changing. Strategies are needed to sustainably manage marine resources in a changing climate. This NMFS Climate Science Strategy will inform living marine resource management. It will guide integration of climate change science across all NMFS mandates.